PENGARUH BOARD INDEPENDENCE, COMPANY SIZE DAN GEARING RATIO TERHADAP RISK DISCLOSURE - Edwin Adhitama, Elsa Imelda (Jurnal Paradigma Akuntansi, 2020)
This research was made with the aim to determine the effect of board independence, company size and gearing ratio on risk disclosure. The study used 140 samples of data from 35 banking companies found on the Indonesia Stock Exchange in 2014-2017 as a whole. Eviews 9.0 is software that is used to process data. The result of this study shows that company size has positive significant effect on risk disclosure while board independence and gearing ratio have insignificant effect on risk disclosure.